Promoting Climate Change Mitigation & Supporting NGOs: Converging the Theory of Planned Behavior & the Elaboration Likelihood Model - Halawa, Passant Mostafa (AUC Knowledge Fountain, 2022)
In the 21st century, public opinion's attention in developed nations has increasingly been directed to climate change and the urgency for humanity to take action. The main discourse is that climate change would have devastating consequences on a global scale, threatening humanity’s existence. However, in most developing countries climate change is generally not regarded as an important topic and climate change messages suffer from poor public engagement. Most recent research has investigated climate change communication efficiency in developed countries. The novelty of this study lies in understanding the effectiveness of climate change messages in the Egyptian context. More specifically this thesis focuses on how appeal types in climate change messages can increase Egyptians’ engagement with climate change messages and promote positive intention towards supporting non-governmental initiatives to mitigate climate change. This study has two objectives. Firstly, it aims at understanding the effectiveness of communication appeals, such as rational, hope, and fear appeals on audiences’ engagement with climate change advertising messages. Secondly, the study examines the effectiveness of attitudes, subjective norms, and perceived behavioral control on participants’ behavioral intention toward climate change mitigation initiatives by non-governmental organizations. To achieve these objectives, a twopronged data collection method was applied. An online experiment was carried out using the Facebook AB testing tool to examine the effectiveness of climate change messages’ appeals type on audience engagement. Findings from this experiment show that fear appeal leads to a higher engagement than ads using rational or hope appeals. In parallel, an online survey was also conducted to examine how Egyptians’ attitude toward climate change, peer pressure, and perceived behavioral control impact Egypt’s citizens intention to support NGOs’ climate change initiatives. Using convenient sampling, 516 responses were collected. Results from the online survey show that attitude and perceived behavioral control are statistically significant and positively correlated to respondents’ intention to support climate change initiatives. It was also found that subjective norms significantly contribute but to a lesser degree to climate change advocacy. The findings of this study provide practitioners and academics with a novel insight into climate change message effectiveness in the Egyptian context. Importantly this study suggests effective methods to raise awareness about the urgency of climate change in developing countries; a region that is predicted to become severely impacted by climate change.